Intralingual Translation and its Implementation on the Example of Slovene - Ulčnik, Natalija (Slavia Centralis, 2023)
The article focuses on the theoretical and practical aspects of intralingual translation, which refers to translation within one national language on the older language-modern language time axis. The translation strategies, which can be seen from the accompanying words to the existing intralingual translations of older Slovenian texts from the 10th and 16th centuries, have been verified and identified on the basis of a comparative analysis of selected source texts (Brižinski spomeniki/Monumenta Frisingensia, Trubar’s Abecednik/Alphabet and Cerkveni red/Church Order) with their translations into contemporary Standard Slovene.
Keywords: older Slovene, contemporary Slovene, source text, target text, intralingual translation, translation strategies